Efeitos da dieta cetogênica na avaliação de parâmetros bioquímicos e clínicos da distrofia muscular de Duchenne: estudo pré-clínico - Fausto, Lílian de Souza Leite (2018)
Introduction: Duchenne muscular dystrophy (DMD) is one of the X-linked recessive progressive muscular dystrophies, characterized by progressive degeneration of skeletal muscle and multisystemic involvement, including the central nervous system (CNS). These processes have a high metabolic cost and are associated with an oxidative and inflammatory process, as well as learning and memory dysfunction. The ketogenic diet (DCet) is a potentially effective treatment for clinically refractory epilepsy and other neurodegenerative disorders, although the mechanisms by which DCet achieves neuroprotection and / or epilepsy control are not yet known. Objective: to investigate the effects of DCet on biochemical and clinical parameters in a mouse model with DMD. Methods: Young adult mice (50 days old) were fed DCet for 14 days; control groups received a standard diet for the same period. On the 14th day of exposure to diets, each mouse was submitted to memory and behavior evaluation tests. After the behavioral tests, the animals were sacrificed for biochemical evaluation of oxidative stress and levels of inflammatory biomarkers. Body weight, feed intake and BDNF levels were also evaluated. Results: mdx+DCet mice had less mass (0.2g ± 2.49) and presented memory retention (p <0.05) in relation to the control group. There was reduction of oxidative damage in muscle tissue and CNS, and significant decrease in cytokine levels (p <0.05). This protocol increased the level of hippocampal BDNF and mitochondrial respiratory complex activity in both muscle tissue and CNS, although it only decreased creatine kinase activity in the striatum. Conclusion: it can be inferred that the use of KD for 14 days protocol can exert protective effects improving spatial learning and memory function likely via attenuation of oxidative stress, immune response and increased BDNF level seen in these animals.